Architectural complexities and morphological variations of the sediment waves of Plio-Pleistocene channel levee backslope of the Indus Fan (Rudarsko-geološko-naftni zbornik, 2022)
The architecture of the turbidity current sediment waves exhibits intricate morphologies and patterns on the Indus Fan channel levee backslope. The sediment waves are present on the channel levee of Plio-Pleistocene age and are absent in the deeper sections of the study area. The architecture of channel levee backslope on the Indus Fan is poorly understood. We used seismic interpretation techniques and modelling by utilizing high-resolution seismic data to approach this problem. The morphological variations in wavelength, crest dimensions and potential wave formation patterns suggest the autogenic and allogenic processes associated with wave development. Wavelengths reach up to 1473 m with an average of 486.84 m and the height of the levee ranges between 10 m and 60 m (average 30 m). The angle of the channel levee and dimension of the sediment wave here are independent of each other. Low angle levees have accommodated high dimension sediment waves and vice versa at multiple points downslope. Characteristically, the waves have formed on the outer levee (usually left) of the channels marked by steep margins suggesting that flow overspill caused the development of the waves. Generally, the younger sediment waves followed the patterns of older sediment waves, but the varying trends are often observed in the study area. The patterns of the sediment waves towards the younger sections of the levee indicate the modified and varying architectural style of growth. Sediment waves are generated by downslope turbidity currents. However, the deformation features have also possibly triggered the development of sediment waves.